Kajian Hukum Islam atas Kewajiban Menuntut Ilmu : Implikasi bagi Sistem Pendidikan Kontemporer - Dyah Erlina Sulistyaningrum; Suryadi Suryadi; Husin Husin (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The obligation to seek knowledge holds a central position in Islamic law, grounded in strong normative and theological principles. Islam classifies the pursuit of knowledge as fardhu ‘ain (an individual duty) for essential religious and worldly knowledge, and fardhu kifayah (a collective duty) for broader societal needs. This article explores the legal foundations of this obligation in Islamic jurisprudence and examines its relevance in the context of contemporary education. Using a normative-juridical method, this study analyzes primary Islamic sources such as the Qur’an, Hadith, and the views of classical and modern scholars. The findings show that Islam does not treat knowledge merely as a tool for personal development, but as a moral and spiritual responsibility. In modern educational systems, these values remain highly relevant, particularly in addressing ethical decline and the loss of purpose in learning. This article recommends the integration of Islamic legal perspectives on knowledge into educational curricula to help restore the spiritual and moral aims